Sporotrichoid lymphocutaneous pattern in a fish‐merchant under immunosuppressant medications: Clues to differential diagnoses - Dhan Keshar Khadka; Ripala Acharya; Sudha Agrawal (Clinical Case Reports, 2022)
Abstract Sporotrichoid‐lymphocutaneous‐pattern is classically seen in sporotrichosis, though also present in other infections like atypical mycobacteriosis and leishmaniasis. Cutaneous atypical mycobacterial infection presents as localized lesions in immunocompetent and is widespread in immunosuppressed patients. Here, we present a case of sporotrichoid‐lymphocutaneous infection due to atypical mycobacteria, in a fish‐seller under immunosuppressants.